Model' organizacii fizkul'turno-ozdorovitel'noj raboty s naseleniem v Respublike Belarus v novych social'no-ekonomiceskich uslovijach - Filippov, N. N. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The theoretical model of physical culture which appropriate to the requirements of the present days, considers as the purpose the formation of harmoniously advanced person described by intensive development various forces on the integrative basis of creative activity. It means the necessity of the strengthening of the variety of contents of various forms of physical culture on the basis of integration of ways of influence to the person.